ThreadED: A Networked Learning Initiative - Kearney, Alison; Mentis, Mandia; Carvalho, Lucila; Hartnett, Maggie; Erueti, Bevan (Proceedings of the International Conference on Networked Learning, 2018)
ThreadED is a networked learning initiative designed to promote connections between teaching staff, students and digitised resources, as well as to support teaching and learning at Massey University Institute of Education in New Zealand. ThreadED is framed around three strands (and related teacher and student competencies) identified by the Institute as important foci for their programmes: equity, cultural responsivity and digital literacy. Resources and artefacts such as website links, articles, videos and apps are being identified, developed and catalogued at various levels of granularity, and linked to key competencies. A platform to archive and curate artefacts and resources has been developed, incorporating design principles that focus on maintaining autonomy and freedom of access to resources, for all teaching staff. Templates were also developed to provide support and guidelines for the annotation of each resource. These resources and artefacts will be used and curated by teaching staff for different teaching and learning purposes, across courses within the Institute of Education. A number of benefits are anticipated when the initiative begins operation in 2018. These include the adoption of the three key foci across all of the teaching programmes within the Institute of Education; the reduction in work and duplication associated with staff each producing the same content in different courses; staff having a greater awareness of each other’s work and a strengthening of relationships; and the creation of synergies between staff that may lead to other opportunities in teaching and research. Finally, it is anticipated that ThreadED will enable personalised, self-directed and flexible teaching and learning practices by allowing teaching staff to select – from a range of quality learning objects – a resource that best meets individual needs and learning goals of the courses that are taught within the Institute. This paper introduces this initiative, discussing its key underlying principles as well as strategies used to facilitate staff’s participation and contributions to a joint venture of knowledge creation. The initiative aims at reframing isolated academic practices at the Institute of Education towards an evolving participatory learning community, where everyone is able to build on each other’s knowledge and expertizes, sharing resources and practices related to equity, cultural responsivity and digital literacy.